Disopyramide Revisited for Treatment of Symptomatic Obstructive Hypertrophic Cardiomyopathy: Efficacy and Safety in Patients Treated for at Least 5 Years - Daniele Massera; Mark V. Sherrid; Elizabeth Adlestein; Nadia Bokhari; Isabel C. Alvarez; Woon Y. Wu; Maria C. Reuter; Martin S. Maron; Barry J. Maron; Ethan J. Rowin (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Disopyramide is used to treat heart failure symptoms in patients with obstructive hypertrophic cardiomyopathy (HCM) with known medium‐term efficacy and safety, while long‐term outcomes are unknown. Methods and Results A total of 92 consecutive patients with symptomatic obstructive HCM with peak left ventricular outflow tract gradients of ≥30 mm Hg at rest or with provocation who were maintained on disopyramide for ≥5 years at 2 dedicated HCM centers were included: 92 patients; mean age, 62.5 years; 54% women; treated with disopyramide for median 7.2 years (left ventricular wall thickness 18±4 mm; median peak outflow gradient 95 mm Hg). At last follow‐up, 62 (67%) patients continued disopyramide, including 57 with symptom improvement ≥1 New York Heart Association class. The other 30 (33%) patients discontinued disopyramide due primarily to incomplete symptom resolution and required surgical myectomy or alcohol septal ablation (n=23) at 7.4 years from initiation. With disopyramide, resting left ventricular outflow gradients were reduced by 37% (to median 19 mm Hg), and provoked gradients decreased by 57% (to median 41 mm Hg), with no residual outflow obstruction (<30 mm Hg at rest or with provocation) in 42 (46%) patients and no change in ejection fraction (69%±6% versus 69%±9%, P=0.51). Ventricular tachyarrhythmias and left ventricular systolic dysfunction were uncommon (n=3 and n=1) and were not attributed to disopyramide. Death on disopyramide was exceedingly rare (n=3 [5%]) and non–HCM‐related occurring at age ≥90 years. Conclusions In patients with obstructive HCM, disopyramide is safe and effective at relieving heart failure symptoms from outflow obstruction in a subgroup of patients who were maintained on disopyramide for >5 years.